O ensino de artes visuais frente à modernidade/colonialidade: a narrativa eurocêntrica dos currículos e uma proposta de aulas oficina desobedientes - AMANDA MAMEDE (2023)
This dissertation starts from the research problem regarding which narrative of art history is present in the curricular documents and teaching manuals that regulate the teaching of visual arts in the city of Campo Grande-MS. Using the deductive method with a qualitative approach in a decolonial perspective, we seek to understand how the construction of curricular references that guide and standardize basic education reflect on the teaching-learning processes, based on the hypothesis that Latin American references are made invisible and delegitimized in art classes, contributing to the maintenance of the coloniality of power (QUIJANO, 2005). Content analyzes are carried out in the Curricular Reference of the Municipal Teaching Network of Campo Grande-MS (Reme) and in selected contents in four volumes (6th to 9th year) of the teacher's manual from the collection “Por Toda pARTE”, from the publisher FTD, adopted by the municipal network for the four-year period 2020-2023; the collection is part of the National Book and Teaching Material Plan (PNLD). It is reflected along with Silva (2013) and Arroyo (2013) in relation to critical theories of the curriculum and its conception of a territory of constant dispute over the tension of knowledge and Bittencourt (2002), Choppin (2004) and Rüsen (2009) about of the didactic manual analysis methodology, considering it a complex and multifaceted instrument. Thus, the general objective of the research is to analyze points of teacher disobedience (MOURA, 2018) regarding the discourse present in the content presented by both analysis instruments and the construction of a teaching material composed of four workshop classes, whose content is disobedient to the modern/colonial logic that prevails over the epistemologies of the South. It was possible to perceive that the Reme Reference is essentially Eurocentric in its contents, especially in relation to the chronology of art history, as well as the narrative inscribed in the discourse of the manuals didactic. Both instruments marginalize movements, works, artists, concepts and trends produced outside the Europe-USA axis, producing an idea of ​​a “culture of repetition” (RICHARD, 2012). Therefore, this dissertation offers didactic material whose objective is to provide teaching tools for the exercise of disobedience to the centralization of Euro-American epistemology in teaching-learning processes in visual arts, turning its gaze to the sociopolitical, cultural and artistic landscape of Mato Grosso do Sul and Mato Grosso, offering a counterattack to education conditioned to capitalist/modern/colonial logic.